2010
DOI: 10.54386/jam.v12i1.1281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weather parameters on karnal bunt disease in wheat in Karnal region of Haryana

Abstract: Data pertaining to average infection (%) of karnal bunt disease of wheat and meteorological parameters of 1st to 12th standard meteorological week (1st January to 25th March) for 25 crop seasons (1981-82 to 2004-05) of Karnal station were correlated to study the effect of weather parameters on Karnal bunt disease in wheat for most sensitive crop growth period corresponding to ear emergence and subsequent growth stages. The frequency of disease intensity and weather parameters indicated that when the maximum te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Two thin layers (in the form of pastes) of dyes D 1 and D 2 capped ZnO nanoparticles were arranged on two different dried transparent ITO conductive glass sheets working as photo‐anodes for the ZnO solar cells assemblies SC 1 and SC 2 respectively. For evaluating photovoltaic parameters of ZnO DSSCs, same dimensions has been maintained 1 cm×1 cm (effective surface area=1 cm 2 ) of the ITO glass sheet as per our previous research work for the DSSCs [44] . The dye molecules capped ZnO based ITO glass sheet was air‐dried at room temperature.…”
Section: Fabrication Of Dyes D1 and D2 Capped Zno Dsscsmentioning
confidence: 99%
“…Two thin layers (in the form of pastes) of dyes D 1 and D 2 capped ZnO nanoparticles were arranged on two different dried transparent ITO conductive glass sheets working as photo‐anodes for the ZnO solar cells assemblies SC 1 and SC 2 respectively. For evaluating photovoltaic parameters of ZnO DSSCs, same dimensions has been maintained 1 cm×1 cm (effective surface area=1 cm 2 ) of the ITO glass sheet as per our previous research work for the DSSCs [44] . The dye molecules capped ZnO based ITO glass sheet was air‐dried at room temperature.…”
Section: Fabrication Of Dyes D1 and D2 Capped Zno Dsscsmentioning
confidence: 99%
“…48 Similar approach was conducted by Singh et al where microwave induced poly(acrylic acid) graed on Cassia javanica (CJ) seed gum revealed as an efficient Hg(II) adsorbent (q m ¼ 135 mg g À1 ). 49 It was proved that method of initiation by high-energy radiation gave signicant advantages over conventional method like high adsorption efficiency and free of initiator.…”
Section: Comparison With Other Adsorbentsmentioning
confidence: 99%
“…Extensive investigations carried out on adsorption of Hg(II) revealed that the adsorption capacity of Hg(II) was strongly influenced by the concentration of the electrolyte ion added to the solution and found that a rise in ionic strength led to a decrease in the Hg(II) uptake capacity because of the decrease in the activity of metal ions and the increase in concentration of competing cations. [35][36][37] Figure 4 presents the effect of the ionic strength on the Hg(II) adsorption capacity. As seen in Figure 4, increasing the ionic strength from 0 to 1 mol L 21 did not lead to a decrease in Hg(II) adsorption.…”
Section: Characterizationmentioning
confidence: 99%